Azure advanced virtual machine deployment - Kennedy, Norm; Safari eBooks ([Place of publication not identified] : [CompuWorks], 2016)
"This course is designed to instruct students on Azure as it pertains to Virtual Networks, Virtual Machines, and Storage capabilities. Students will understand ARM vs. Classic deployment, review the advantages of ARM, and work with ARM deployment methods. Students will use ARM templates, understand RBAC, work with Azure ARM load balancer and use ARM scale sets. In addition, students will create an automation account, assets, and runbooks."--Resource description page.
Presenter, Norm Kennedy.
Title from title screen (viewed November 15, 2016).
Imprint from resource description page.
Keywords: Virtual computer systems; Computer networks -- Management; Computer storage devices; Electronic books